ANTIUROLITHIATIC ACTIVITY OF ETHANOLIC EXTRACT OF TAXILLUS TOMENTOSUS PLANT ON ETHYLENE GLYCOL AND AMMONIUM CHLORIDE INDUCED UROLITHIASIS IN WISTAR RATS - Kambham Venkateswarlu; Jami Komala Preethi; K. B. Chandrasekhar (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
The present study investigates the potential of anti-urolithiatic activity of ethanolic extract of Taxillus tomentosus plant (EETT). Urolithiasis was induced by feeding the 0.75% of Ethylene glycol (EG) and 2% of Ammonium chloride (AC) in drinking water along with the normal feed in male wistar rats and then the anti-urolithiatic activity of EETT was evaluated. Acute toxicity study was conducted by LD50 cutoff dose of 2000mg/kg body weight (BW), indicates that the drug to be much safer and 1/10th (200mg/kg BW) and 1/5th (400mg/kg BW) of LD50 doses were selected for study. Serum and urine samples were analyzed for knowing the concentration of creatinine, calcium, urea, uric acid, oxalates and during the entire study, urolithiatic animals showed significantly high concentrations than normal animals. The EETT (200mg/kg BW and 400mg/kg BW) was showed good response to antiurolithiatic activity when compared to the standard drug cystone (CST).Keywords: anti-urolithiatic activity, taxillus tomentosus, ethylene glyco, ammonium chloride, cystone.